2020
DOI: 10.1101/2020.03.23.20041814
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Population-Level Mortality Rates from Novel Coronavirus (COVID-19) in South Korea

Abstract: Background: South Korea was among the first countries to report a case of the novel coronavirus (COVID-19) outside of China. As of 22 March, 2020, South Korea reported 8897 confirmed cases of and 104 deaths from COVID-19. Methods:We collected the number of laboratory-confirmed cases and deaths in South Korea from the World Health Organization (as of 21 March, 2020) and case distribution and fatality rates by age from the Korean Center for Disease Control and Prevention (as of 22 March, 2020). We estimated popu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 10 publications
0
9
1
Order By: Relevance
“…Other studies have shown similar prevalence of infection among young HCW. In South Korea 26.9% of cases occurred among HCW aged 20–29 years [ 17 , 18 ]. Risk increases when comorbidities are present, which poses important implications for occupational infections of HCW in hospital settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have shown similar prevalence of infection among young HCW. In South Korea 26.9% of cases occurred among HCW aged 20–29 years [ 17 , 18 ]. Risk increases when comorbidities are present, which poses important implications for occupational infections of HCW in hospital settings.…”
Section: Discussionmentioning
confidence: 99%
“…The most significant initial symptoms reported by those testing positive were headache (22.95%), body aches/discomfort (15.57%), cough (13.93%), sore throat (13.93%) and fever (12.30%), which are considered the most common symptoms associated with COVID-19 [ 18 , 28 ]. Among all those infected with SARS-CoV-2, 54.92% were asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…However, initial studies from China and Italy indicated that the majority of COVID-19 patients were elderly [104,105]. In contrast, in more recent reports from South Korea, most SARS-CoV-2 infections occurred in individuals aged 20-29 years [106]. The discrepancies of age distribution in COVID-19 cases may be explained by differences in testing strategies and other factors.…”
Section: Role Of Endothelial Dysfunction In Sars-cov-2 Infections: CImentioning
confidence: 99%
“…Baud and others, 2020;Begley, 2020, Belligoni, 2020Courage, 2020;Dylan, 2020;Huang and others, 2020;Mahase, 2020; Onder and others, 2020;Richardson andothers, 2020, Soneji and Wu and McGoogan, 2020. 5 Istituto Superiore diSanità, 2020; Korean Ministry of Health and Welfare, 2020; Spanish Ministry of Health, 2020.…”
mentioning
confidence: 99%